Training the Honest Character of the Child at Home - Imam Tabroni; Fitriani Nasihah (PT FORMOSA CENDEKIA GLOBAL, 2023)
The weakening of honest character requires an increase in the intensity and quality of the implementation of character education in the formal and non-formal institutions. However, in reality, it is not only formal or non-formal institutions that are responsible for shaping the honest character of children, but the most dominant thing to shape the character of children is their families, especially parents. This study aims to provide an overview of how to train honest character in children at home. The research conducted is PAR-based, where the researcher directly participates in the actions carried out. Data collection through observation, interviews, and documentation. Before the action was taken, there were several problems regarding the child's incompetence, such as not telling the truth, taking things that did not belong to him, not being entrusted with the task given, being reluctant to apologize after making a mistake, and not wanting to admit mistakes. Thus, action is needed to train children to have an honest character because honesty is the basic capital in life. Some of the actions taken to train honest character at home are through democratic types of parenting, providing teaching, setting an example, and giving positive appreciation to children. In addition, parents must have a high and consistent commitment to honest character training in children at home.